Analisis faktor risiko diabetes mellitus pada remaja - Masdaf, Agino Saputra; Nurhusna, Nurhusna; Sari, Putri Irwanti; Oktarina, Yosi; Sari, Yulia Indah Permata (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Diabetes mellitus in adolescents continues to increase due to modern lifestyles characterized by unhealthy diets, low physical activity, and obesity. Purpose: To analyze the relationship between physical activity, diet, and obesity (BMI) and the risk of diabetes mellitus in adolescents. Method: A quantitative, cross-sectional analytical study of 101 eleventh-grade respondents was conducted using purposive sampling. Instruments included the Global Physical Activity Questionnaire (GPAQ), Food Frequency Questionnaire (FFQ), anthropometric measurements, and the Finnish Diabetes Risk Score (FINDRISC). Data analysis used frequency distribution and the Gamma test with α = 0.05. Results: The majority of respondents were aged 16-18 years (86.1%), female (59.4%), reported light physical activity (43.6%), had poor diet (50.5%), had a normal BMI (34.7%), and had a low risk of diabetes mellitus (84.2%). The Gamma test results showed a significant association between physical activity (p = 0.002; OR = 0.690), diet (p = 0.005; OR = 2.105), and BMI (p = 0.011; OR = 13.778) and the risk of diabetes mellitus. Conclusion: There is a significant association between physical activity, diet, and BMI and the risk of diabetes mellitus in adolescents.   Keywords: Adolescents; Body Mass Index; Diabetes Mellitus; Eating Patterns; Physical Activity.   Pendahuluan: Diabetes mellitus pada remaja terus meningkat akibat gaya hidup modern yang ditandai oleh pola makan yang tidak sehat, rendahnya aktivitas fisik, dan obesitas. Tujuan: Untuk menganalisis hubungan antara Aktivitas fisik, pola makan, dan obesitas (IMT) dengan risiko Diabetes Mellitus pada remaja. Metode: Penelitian kuantitatif analitik cross-sectional pada 101 responden kelas XI dengan purposive sampling. Instrumen meliputi Global Physical Activity Questionnaire (GPAQ), Food Frequency Questionnaire (FFQ), pengukuran antropometri, dan Finnish Diabetes Risk Score (FINDRISC). Analisis data menggunakan distribusi frekuensi dan uji Gamma dengan α = 0,05 Hasil: Mayoritas responden berusia 16-18 tahun (86.1%), perempuan (59.4%), aktivitas fisik ringan (43.6%), pola makan kurang baik (50.5%), IMT normal (34.7%), dan risiko diabetes melitus rendah (84.2%). Hasil uji Gamma menunjukkan hubungan signifikan antara aktivitas fisik (p = 0.002; OR = 0.690), pola makan (p = 0.005; OR = 2.105), dan BMI (p = 0.011; OR = 13.778) dengan risiko diabetes melitus Simpulan: Terdapat hubungan yang signifikan antara aktivitas fisik, pola makan, dan IMT dengan risiko diabetes mellitus pada remaja.   Kata Kunci: Aktivitas Fisik; Diabetes Mellitus; Indeks Massa Tubuh; Pola Makan; Remaja.